COLONEL PARKER’S NEW WOMAN AND THE NEW EDUCATION - Campbell, Jack K. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1975)
The marriage in 1882 of Mary Frances Stuart and Colonel Francis w. Parker symbolized the union of the feminist movement with that of educational reform. History has somehow overlooked the impact of the woman’s movement on the progressive transformation of the schools during the late 19th and early 20th centuries, but the liberation of women and children from the bondage of tradition was a common struggle. Sorne of the educational and social theories of Colonel Parker, acknowledged father of the movement which would be called Progressive Education, were inspired by his New Woman. Moreover, the refinement of his ideas rested largely on Mrs. Parker’s artistic genius, and the political support so necessary for their implementation depended to a considerable degree on her connections with women’s organizations. As queen of such clubs, Mrs. Parker was the trump in the power play for the Colonel’s educational aims. She represents the forgotten half, and perhaps the better half, of the conception and birth of Progressive Education.